Nutrient Manager for Rice (NMRiceMobile) - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
NMRiceMobile is designed to help farmers increase their production and profit by allowing them to receive advice via their mobile phone on applying the right type of fertilizer in the right amount and at the optimum time, thereby reducing fertilizer waste. It incorporates the principles of site-specific nutrient management (SSNM) for rice already well  established  in  Asia’s  major  rice-growing areas. SSNM is available through an online decision-making tool called Nutrient Manager for Rice, which is tailored to the particular rice-growing conditions of a country. It enables extension workers, crop advisors, and farmers to rapidly determine the best fertilizer management practice for specific areas. Online applications of Nutrient Manager for Rice are now available for the Philippines, Indonesia, and Guangdong Province of China.